2021
DOI: 10.3390/nano11020526
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Activity of Magnetic Nano-β-FeOOH/Fe3O4/Biochar Composites for the Enhanced Degradation of Methyl Orange Under Visible Light

Abstract: A novel nano-β-FeOOH/Fe3O4/biochar composite with enhanced photocatalytic performance and superparamagnetism was successfully fabricated via an environmentally friendly one-step method. The structural properties of the prepared composite were characterized by scanning electron microscopy, transmission electron microscopy, energy-dispersive spectroscopy, X-ray photoelectron spectroscopy, and a vibrating sample magnetometer. The XPS spectrum of the as-prepared composites confirmed the presence of Fe-O-C bonds be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The increase in the ID/IG ratio suggested an increase in the defect degree, which can be attributed to the formation of MnO 2 particle clusters within the BC structure. Similarly, a prior study [ 40 ] reported an ID/IG ratio increase when β-FeOOH/Fe 3 O 4 nanoparticles were added to BC. They assigned this increase to the reduction in the carbon sp 2 domain and justified that the β-FeOOH/Fe 3 O 4 nanoparticles formed and grew on the graphitic structure of the material.…”
Section: Resultsmentioning
confidence: 56%
“…The increase in the ID/IG ratio suggested an increase in the defect degree, which can be attributed to the formation of MnO 2 particle clusters within the BC structure. Similarly, a prior study [ 40 ] reported an ID/IG ratio increase when β-FeOOH/Fe 3 O 4 nanoparticles were added to BC. They assigned this increase to the reduction in the carbon sp 2 domain and justified that the β-FeOOH/Fe 3 O 4 nanoparticles formed and grew on the graphitic structure of the material.…”
Section: Resultsmentioning
confidence: 56%
“…XPS demonstrated that Fe, C, O, and N elements were present on the Fe 3 O 4 @EDTA–Fe 2+ nanoparticle surface (Figure B). The typical doublet photoelectron peaks of Fe at 724.40 and 710.9 eV in the XPS profile of the pristine nanoparticles could be assigned to the Fe 2p 1/2 and Fe 2p 3/2 components, respectively (Figure C) . Each peak could be sud-divided into two peaks, which accounted for the simultaneous contribution of Fe 2+ and Fe 3+ .…”
Section: Resultsmentioning
confidence: 96%
“…The typical doublet photoelectron peaks of Fe at 724.40 and 710.9 eV in the XPS profile of the pristine nanoparticles could be assigned to the Fe 2p 1/2 and Fe 2p 3/2 components, respectively (Figure 2C). 23 Each peak could be sud-divided into two peaks, which accounted for the simultaneous contribution of Fe 2+ and Fe 3+ . 24 In the C 1s spectrum, the increase in the relative content of C−O and O− CO in Fe 3 O 4 @EDTA and Fe 3 O 4 @EDTA−Fe 2+ compared to that in the pristine Fe 3 O 4 nanoparticles could be assigned to the carboxyl group, which confirmed successful formation of the EDTA layer on the surface of the nanoparticles (Figure S2A and Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Green algae, as source material for biochar, represents a sustainable and renewable resource, as it can be cultivated in various water bodies, including those unsuitable for other uses 37 42 . Algae-based biochar, especially when modified, can have a high surface area and porosity, making it highly effective for adsorbing pollutants, including heavy metals, dyes, and organic compounds from wastewater 28 , 43 45 . Moreover, it emphasizes that the presence of N-functional groups in algae-based biochar improved its surface chemistry and adsorption capacity 46 .…”
Section: Introductionmentioning
confidence: 99%